2017
DOI: 10.3390/en10030391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Analysis and Forecasting for Security Early Warning of Energy Consumption Carbon Emissions in Hebei Province, China

Abstract: Against the backdrop of increasingly serious global climate change and the development of the low-carbon economy, the coordination between energy consumption carbon emissions (ECCE) and regional population, resources, environment, economy and society has become an important subject. In this paper, the research focuses on the security early warning of ECCE in Hebei Province, China. First, an assessment index system of the security early warning of ECCE is constructed based on the pressure-state-response (P-S-R)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
5
0
3
Order By: Relevance
“…From the review of the literature, this kind of study has been shown to be relevant to other past research in terms of model applications in CO 2 emission forecasting. Zhao, Zhao, and Guo [9] used GM (1,1) optimized by MFO with a rolling mechanism to forecast the electricity consumption of Inner Mongolia; Chang, Sun, and Gu [13] forecast energy CO 2 emissions using a quantum harmony search algorithm-based DMSFE combination model; Zeng, Xu, Wang, Chen, and Li [14] forecasted the allocative efficiency of carbon emission allowance financial assets in china at the provincial level in 2020; Liang, Niu, Wang, and Chen [15] did an assessment analysis and forecast for the secure early warning of energy consumption carbon emissions in Hebei Province, China; Li, Yang, and Li [30] forecast China's coal power installed capacity using a comparison of MGM, ARIMA, GM-ARIMA, and NMGM Models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the review of the literature, this kind of study has been shown to be relevant to other past research in terms of model applications in CO 2 emission forecasting. Zhao, Zhao, and Guo [9] used GM (1,1) optimized by MFO with a rolling mechanism to forecast the electricity consumption of Inner Mongolia; Chang, Sun, and Gu [13] forecast energy CO 2 emissions using a quantum harmony search algorithm-based DMSFE combination model; Zeng, Xu, Wang, Chen, and Li [14] forecasted the allocative efficiency of carbon emission allowance financial assets in china at the provincial level in 2020; Liang, Niu, Wang, and Chen [15] did an assessment analysis and forecast for the secure early warning of energy consumption carbon emissions in Hebei Province, China; Li, Yang, and Li [30] forecast China's coal power installed capacity using a comparison of MGM, ARIMA, GM-ARIMA, and NMGM Models.…”
Section: Discussionmentioning
confidence: 99%
“…With that, they therefore provided a suggestion of which particular provinces have to cut off their CO 2 emission. Also, Liang, Niu, Wang and Chen [15] did an evaluation on the security early warning of energy consumption carbon emissions (ECCE) in Hebei Province of China. They constructed an assessment index system according to the pressure-state-response (P-S-R) model, as well as deploying the variance method and linearity weighted method in order to compute such an early warning index of ECCE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lastly, the solutions in FB are put in order and the best solution is updated. The filtration rate is updated and FB and W are merged (Jaddi et al, 2017; Liang et al, 2017; Taqi and Ali, 2017). When the termination condition is satisfied, this iterative process stops.…”
Section: Kamentioning
confidence: 99%
“…Bu özelliği sayesinde iyi bir yakınsama performansı gösterir [11]. Yeni bir algoritma olmasından ötürü, birkaç mühendislik uygulaması [13][14][15][16][17]…”
Section: Introductionunclassified